AB0461 The burden of behçet's disease in the south thames and, se coast regions – a regional review. (23rd January 2014) - Yalakki Jagadeesh, L.; Hepburn, A.; Hughes, R.; Bourke, B.; Garood, T.; Horwood, N.; Ewence, A.; Lloyd, M.; Makanjuola, D.; Reilly, P.; Moss, K.; Hajela, V.; et al.
Abstract : Background: Behcet's disease(BD) is a rare inflammatory disorder of unknown aetiology, with estimated prevalence of 1- 2 per 100, 000 in the UK. In routine clinical practice patients with BD present challenges given the lack of a specific diagnostic test and the complexity of potential organ and life threatening complications. Objectives: To perform a multicentre survey of patients with BD, focussing on diagnostic delay, use of HLA B51, prevalent clinical manifestations and range of therapies utilised. Methods: A standardised data collection proforma was circulated to rheumatology consultants in London South, Surrey and West Sussex regions. Information collected included demographic details, time from first symptom to diagnosis, HLA B51 status, the spectrum of phenotypic manifestations and range of treatments used. Results: Fourteen consultants from 8 hospitals returned completed proformas on 46 patients. 54.3% were female, median age 40 years (range 17 – 72), 56.5% Caucasian, 15% Afro-caribbean and 53% non smokers. The median age of symptom onset was 28 years (range 10 – 60) and the median diagnostic delay was 2 years (range 0 – 20). The pathergy reaction was recorded as positive in 24%(11/45).HLA B51 had been measured in 45.5%(21/46) and was positive in 24%(5/21). The prevalence of clinical phenotypes was: mouth ulcers 98%, genital ulcers 80%, cutaneous lesions 78%, joints 74%, central nervous system 65%, ocular 37%, vascular 28% (arterial 30.7% venous 69.2%), gastrointestinal 20% and peripheral nervous system 17%. In addition to oral and genital ulceration a median of 3(range 1 – 6) additional systems were involved in each patient. The commonest treatments used were oral/parenteral steroids 91%, azathioprine 54% and colchicine 52%. Less frequently used were methotrexate 25%, mycophenolate mofetil 15% and Ciclosprin A 10%. Joint involvement was significantly more frequent in females than males(68% vs 32%, p 0.002) and non significantly higher in Caucasians vs non-Caucasians (65% vs 35%). There was a trend for a higher prevalence of erythema nodosum in females 73% vs 27%. Conclusions: This work shows the value of collaborative regional review in rare conditions like BD. In S. Thames/SE coast the disease impacts young people and many experience a worrying delay of up to 20 years(2 cases), median 2 years, to diagnosis and treatment. HLA B51 testing was utilised as a diagnostic aid in less than half, and the pathergy reaction was infrequent. In this mixed racial, urban and rural population, Afro Caribbean cases made up 15% of the cohort suggesting vigilance in all racial groups is important. In addition to mucosal disease, involvement of a median of 3 additional systems was recorded, indicating the complexity of disease management. The wide range of treatments used reflects the thin evidence base for BD; however it is encouraging that funding for anti-TNF therapy was secured in 17%, in an era before the current National commissioning arrangements were commenced. Disclosure of Interest: None Declared